Factors that Affect Employee Performance - Nasrah, Rasidah; Nirwana, Ida; Razaq, Al Fadhil Abdul (INOVATOR, 2024)
This research aims to determine (1) The influence of personality on the performance of Solok Regency Tourism and Culture Service employees (2) The influence of work orientation on the performance of Solok Regency Tourism and Culture Office employees (3) The influence of employee placement on the performance of Solok Regency Tourism and Culture Office employees.This research was conducted on the performance of Solok Regency Tourism and Culture Office employees. The type of research used is quantitative descriptive research. The data used is primary. The results of the research show that: (1) Personality influences the performance of Solok Regency Tourism and Culture Department employees, as evidenced by the tcount value of 3.977 which is greater than ttable at the 5% significant level, namely 2.01410, so 3.977 > 2.01410 and the probability value is significant equal to (0.000 < 0.05); (2) Work orientation influences the performance of Solok district Tourism and Culture Department employees, as evidenced by the tcount value of 4.031 which is greater than ttable at the 5% significant level, namely 2.01410, so 4.031 > 2.01410 and the significant probability value is (0.000 < 0.05); (3) Employee placement influences the performance of Solok Regency Tourism and Culture Department employees, as evidenced by the tcount value of 3.003 which is greater than ttable at a significant level of 5%, namely 2.01410, so 3.003 > 2.01410 and the significant probability value is (0.004 < 0.05); (4) Personality, Work Orientation, and Employee Placement on the Performance of Solok Regency Tourism and Culture Office Employees, with a coefficient of determination (R2) of 0.822 or 82.2%, and the remaining 17.8% is influenced by other variables outside the variables in this research, such as motivation, service quality, and others.